Effect of juvenile social isolation on excitability of prefrontal pyramidal cells with different subcortical axonal projections - Nishihata, Yosuke; Yoshino, Hiroki; Ogawa, Yoichi; Sugimura, Taketoshi; Okamura, Kazuya; Kimoto, Sohei; Yamamuro, Kazuhiko; Makinodan, Manabu; Saito, Yasuhiko; Kishimoto, Toshifumi (Frontiers in Cellular Neuroscience, 2025)
BackgroundSocial experience during development is crucial for the functional maturation of the prefrontal cortex (PFC). Juvenile social isolation (JSI) causes severe PFC dysfunction. JSI reduces intrinsic excitability and excitatory synaptic inputs for a subtype of layer-5 (L5) pyramidal cells showing prominent h-current (PH cells) in the medial PFC. PH cells do not have commissural or associational cortical output; instead, they project into subcortical areas. However, which subcortical area is the projection target of L5 pyramidal cells affected by JSI remains unascertained.MethodsUsing retrograde neuronal tracing, we identified L5 pyramidal cells having three different projection targets: the mediodorsal thalamus, striatum, or pontine nuclei. We elucidated differences in functional properties among the three subclasses of L5 pyramidal cells and examined how JSI affects the intrinsic membrane properties and excitatory inputs for each class of L5 pyramidal cells.ResultsPyramidal cells projecting to the pontine nuclei had more excitatory synaptic inputs and more distinguishing intrinsic properties than pyramidal cells projecting to the mediodorsal thalamus and striatum. JSI increased the firing responsiveness of pyramidal cell projecting to mediodorsal thalamus and reduced excitatory synaptic inputs only onto pyramidal cells projecting to the pontine nuclei.ConclusionJSI affects the development of L5 pyramidal cells based on their projection target.